2022
DOI: 10.1175/bams-d-21-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Generated Tornadic Vortices

Abstract: Fire-generated tornadic vortices (FGTVs) linked to deep pyro-convection, including pyrocumulonimbi (pyroCbs), are a potentially deadly, yet poorly understood wildfire hazard. In this study we use radar and satellite observations to examine three FGTV cases during high impact wildfires during the 2020 fire season in California, USA. We establish that these FGTVs each exhibit tornado-strength anticyclonic rotation, with rotational velocity as strong as 30 m s-1 (60 kts), vortex depths of up to 4.9 km AGL, and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…As mentioned above, R gf is computed while taking into account the different effective light paths in the respective spectral ranges of HCHO and CHOCHO retrievals, thereby eliminating radiative transfer effects. A similar CHOCHO depletion has been observed for other elevated fire plumes in Australia (e.g., on 30-31 December 2019 and 5 March 2019) and in California during intense fire episodes with reported PyroCb formation (Lareau et al, 2022). This is illustrated in Figure S2 in Supporting Information S1 for the Creek fire of 5 September 2020.…”
Section: Glyoxal Variability Near Fire Sourcessupporting
confidence: 83%
“…As mentioned above, R gf is computed while taking into account the different effective light paths in the respective spectral ranges of HCHO and CHOCHO retrievals, thereby eliminating radiative transfer effects. A similar CHOCHO depletion has been observed for other elevated fire plumes in Australia (e.g., on 30-31 December 2019 and 5 March 2019) and in California during intense fire episodes with reported PyroCb formation (Lareau et al, 2022). This is illustrated in Figure S2 in Supporting Information S1 for the Creek fire of 5 September 2020.…”
Section: Glyoxal Variability Near Fire Sourcessupporting
confidence: 83%
“…Second, wind speed and mid‐tropospheric moisture could be too low to support the observed vertical development of the plume. For example, the HRRR profile shown in L22 suggests stronger wind and slightly moister mid‐troposphere in comparison to the GFS data that were used in this study (not shown). However, examining environmental factors in the development of pyroCb is out of the scope of this study.…”
Section: Summary and Discussionmentioning
confidence: 59%
“…NEXRAD radar data reveal that the pyroCb‐topped plume comprised an updraft core with “overshooting” plume tops reaching ∼15.5 km MSL and a broader shield of lower plume/cloud tops extending northward from the fire (Figures 1b–1d). The condensation level was at ∼5.5 km MSL (L22), meaning the pyroCb portion of the plume was ∼10 km deep. The condensation level was determined based on the Reno, NV sounding from HRRR output by finding the level where the adiabatically raised surface parcel reaches saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Cb-like) and counterintuitive. Conventional lightning, hail, downdraft wind hazards, and even tornadoes have been observed 13,14,[16][17][18] . However, the lack of precipitation and associated scavenging 19 supports intensive downwind fire spotting at the surface and intense in-cloud smoke infusion, such that the skin of the pyroCb typically has a smoky tinge (Fig.…”
mentioning
confidence: 99%
“…The state of knowledge in this regard is incomplete. Notable hints into the internal peculiarity of the pyroCb engine have been established, in terms of updraft speed 15 , circulation 17,18 , lightning 13,70 , and microphysics 13 . Strategically building on this foundation will involve blending the knowledge base manifested in a pyroCbdetection climatology with wildfire data and penetrative data, such as operational and research cloud radar archives.…”
mentioning
confidence: 99%